2012
DOI: 10.1088/1367-2630/14/6/063033
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Coulomb drag for massless Dirac fermions

Abstract: Coulomb drag between two unhybridized graphene sheets separated by a dielectric spacer has recently attracted considerable theoretical interest. We first review, for the sake of completeness, the main analytical results which have been obtained by other authors. We then illustrate pedagogically the minimal theory of Coulomb drag between two spatially separated two-dimensional systems of massless Dirac fermions which are both away from the chargeneutrality point. This relies on second-order perturbation theory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 78 publications
(166 reference statements)
10
75
0
Order By: Relevance
“…47 to include effects due to the finite width of the GaAs quantum well (see Supplementary Note 4). This shows that the experimental results in this temperature range are consistent with the canonical Fermi-liquid prediction 24,[43][44][45][46][47][48][49][50] , that is, R D pT 2 (see also Fig. 3a), as constrained by the available phase-space of the initial and final states involved in the scattering process.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…47 to include effects due to the finite width of the GaAs quantum well (see Supplementary Note 4). This shows that the experimental results in this temperature range are consistent with the canonical Fermi-liquid prediction 24,[43][44][45][46][47][48][49][50] , that is, R D pT 2 (see also Fig. 3a), as constrained by the available phase-space of the initial and final states involved in the scattering process.…”
Section: Resultssupporting
confidence: 80%
“…Figure 2d shows the plots of R D for 30 KrTr50 K, with the 2DEG used as the drive (black points) or passive (red points) layer. It also reports calculations of the temperature dependence of R D in a hybrid Dirac/Schrödinger SLG/2DEG double layer within a Boltzmanntransport theory, which is justified in the Fermi-liquid regime 47,48 . This is done by generalizing the theory of ref.…”
Section: Resultsmentioning
confidence: 99%
“…The strongly doped, Fermi-liquid regime has attracted the most attention in literature. Most authors report the standard ρ D ∼ T 2 n −3 d −4 behavior (Amorim and Peres, 2012;Carrega et al, 2012;Hwang et al, 2011;Katsnelson, 2011;Narozhny et al, 2012; assuming the energy-independent impurity scattering time.…”
Section: B Static Screening For Intermediate Interaction Strengthmentioning
confidence: 99%
“…Both papers reported a stronger dependence of the drag coefficient on the carrier density and interlayer separation, ρ D ∼ T 2 n −4 d −6 . This result was later disputed in ; Carrega et al (2012);and Narozhny et al (2012). These authors showed that the energy (or momentum) dependence of τ is qualitatively irrelevant for the asymptotic behavior of ρ D .…”
Section: Energy-dependent Scattering Timementioning
confidence: 99%
See 1 more Smart Citation